Effect of some develop kinesthetic variables in mastery learning on learning and retaining various swimming styles - Adel, Omer (Journal of Physical Education, 2010)
Learning mastery is a style which take's into a count individual differences. Mastery tends to a chive mastery in learning by developing some kinesthetic perception variables in mastery and given more time and practice and feed back to pupils how need it in order to a chive high distinction grades to all experimental group. The two researches aim where: 1-knowing the effect of developing mastery kinesthetic programs in order to minimize individual differences. 2- The effect of using mastery kinesthetic programs on learning and retaining various swimming styles. Consequently the hypotheses of the study where: 1-There are statically significant differences on the developed kinesthetic variables between both of pre-post test in favor of post test. 2- There are statically significant differences between both of pre and post test in mastery kinesthetic learning various swimming styles in favor of post test. A premeditated homogenous sample was chosen it consists of 20 adults who study physical education at Baghdad university ,the sample was divided in two groups of (10) adults for each group. Statistic treatment: Arithmetic mean-test(t). The result of both gropes experimental and controlled showed significant differences between both of post-test of the the study variables and skill performance to the experimental group with mastery kinesthetic learning. The study there for ,recommends to use mastery kinesthetic learning to learn and retain various swimming styles